Daytime naps can be used to supplement night-time sleep in athletes. (3rd June 2018) - Romyn, Georgia; Lastella, Michele; Miller, Dean J.; Versey, Nathan G.; Roach, Gregory D.; Sargent, Charli
ABSTRACT: This study examined the efficacy of daytime napping to supplement night-time sleep in athletes. Twelve well-trained male soccer players completed three conditions in a randomised, counterbalanced order: 9 h in bed overnight with no daytime nap (9 h + 0 h); 8 h in bed overnight with a 1-h daytime nap (8 h + 1 h); and 7 h in bed overnight with a 2-h daytime nap (7 h + 2 h). Sleep was assessed using polysomnography. The total amount of sleep obtained in the three conditions was similar, i.e. 8.1 h (9 h + 0 h), 8.2 h (8 h + 1 h), and 8.0 h (7 h + 2 h). Daytime napping may be an effective strategy to supplement athletes' night-time sleep.